(untitled) (Web of Teachers: Inderscience Research, 2024)
The distinction between what to think and how to think, as well as the importance of monitoring one’s thoughts, has been emphasized by scholars and educators. Critical thinking is characterized by the ability to reflect on our thought processes, make sound decisions, and think logically. This article aimed to develop critical thinking skills in TEFL students by providing them with short stories to read. To achieve this, a sample TOEFL reading comprehension test was used to select 40 homogeneous students from a pool of 93. These students were randomly divided into two groups of 20: a control group and an experimental group. After a two-month treatment period, the results showed that the experimental group significantly outperformed the control group. Consequently, reading short stories proved to be effective tools for developing critical thinking skills. The study concluded that short stories can foster critical thinking skills and should therefore be included in the educational curriculum.